2022
DOI: 10.3762/bjoc.18.73
|View full text |Cite
|
Sign up to set email alerts
|

A trustworthy mechanochemical route to isocyanides

Abstract: Isocyanides are hardly produced, dramatically sensitive to purification processes, and complex to handle as synthetic tools. Notwithstanding, they represent one of the most refined and valuable compounds for accessing sophisticated and elegant synthetic routes. A unique interest has always been addressed to their production, though their synthetic pathways usually involve employing strong conditions and toxic reagents. The current paper intends to provide a conceptually innovative synthetic protocol for mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The compound proved very effective for dehydrating oximes under mechanochemical acidic Beckmann conditions [44]. Moreover, it represents a suitable and compatible means in the view of a one-pot methodology for preparing isocyanides directly from amines [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound proved very effective for dehydrating oximes under mechanochemical acidic Beckmann conditions [44]. Moreover, it represents a suitable and compatible means in the view of a one-pot methodology for preparing isocyanides directly from amines [56].…”
Section: Resultsmentioning
confidence: 99%
“…In our effort to develop green and sustainable methodologies using mechanochemistry [43][44][45][46], we recently studied a protocol for synthesizing isocyanides using p-tosyl chloride (Ts-Cl) in basic conditions, starting from the corresponding formamides [47]. In this work, we aimed to set compatible conditions to access formamides, envisioning the possibility of generating the isocyanide in a one-pot, two-step reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Another halogenated molecule, 2,3-dichloro-5,6-dicyano-1,4benzoquinone (DDQ), proved to be an appropriate oxidant for C-N couplings towards the synthesis of 1,2-disubstituted benzimidazoles and quinazolin-4(3H)-one derivatives under mechanochemical conditions, as evidenced by Mal and co-workers (Scheme 5) [9]. However, the findings within Mechanochemistry III span beyond the synthesis or the use of halogenated compounds and include the mechanochemical preparation of isocyanides [10], formylated and acetylated amines [11], and the mechanosynthesis of unsymmetrical salens ligands for preparing metal-salen catalysts [12]. This illustrates the broad applicability of mechanochemical activation to advance chemical synthesis on various fronts.…”
Section: N-halosuccinimides Were Also Key Reagents To Develop the Mec...mentioning
confidence: 99%
“…However, the findings within Mechanochemistry III span beyond the synthesis or the use of halogenated compounds and include the mechanochemical preparation of isocyanides [ 10 ], formylated and acetylated amines [ 11 ], and the mechanosynthesis of unsymmetrical salens ligands for preparing metal–salen catalysts [ 12 ]. This illustrates the broad applicability of mechanochemical activation to advance chemical synthesis on various fronts.…”
mentioning
confidence: 99%
“…Remarkably, different reactions involve the use of formamides as starting materials, among which the synthesis of isocyanides represents one of the most important topics in recent years [ 9 , 10 , 11 , 12 , 13 , 14 ]. In this regard, our team’s recent publication has depicted an efficient mechanochemical synthesis of isocyanides starting from formamides [ 15 ], again proving the undeniable relevance of mechanochemistry in the panorama of organic synthesis [ 16 , 17 ]. Furthermore, previous studies have demonstrated the potential utility of this class of compounds for successfully synthesizing amidines [ 18 ], symmetrical and not symmetrical ureas [ 19 , 20 ], isocyanates [ 21 ], and heterocycles [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%